The Utilization of Various Medicinal Plants based on the Dayak Community Perspective in The Central Kalimantan as an Education for Sustainable Development - Fathul Zannah (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Indonesia has abundant biodiversity, especially in Central Kalimantan. One of the ways to explore biodiversity in Central Kalimantan is as a biopharmaceutical, but the results of this exploration are very minimally applied as a learning resource. This study aims to explore the medicinal plants typical of Central Kalimantan used by the Dayak people, especially in the field of cosmetic dermatology. This study uses a qualitative research method with an ethnographic approach. The result`s showed that there were 11 plant species that were used by various sub-ethnic Dayak tribes in Central Kalimantan to treat various diseases, especially for skin health and beauty. The results of these studies can be used as a source of learning in lecture activities as a form of continuing education.